Laboratory characterization of invasive Haemophilus influenzae isolates from Nunavut, Canada, 2000–2012. Issue 1 (1st January 2016) - Tsang, Raymond S. W.; Li, Y. Anita; Mullen, Angie; Baikie, Maureen; Whyte, Kathleen; Shuel, Michelle; Tyrrell, Gregory; Rotondo, Jenny A. L.; Desai, Shalini; Spika, John
Abstract : Background: With invasive Haemophilus influenzae serotype b (Hib) disease controlled by vaccination with conjugate Hib vaccines, there is concern that invasive disease due to non-serotype b strains may emerge. Objective: This study characterized invasive H. influenzae (Hi) isolates from Nunavut, Canada, in the post-Hib vaccine era. Methods: Invasive H. influenzae isolates were identified by conventional methods at local hospitals; and further characterized at the provincial and federal public health laboratories, including detection of serotype antigens and genes, multi-locus sequence typing and antibiotic susceptibility. Results: Of the 89 invasive H. influenzae cases identified from 2000 to 2012, 71 case isolates were available for study. There were 43 serotype a (Hia), 12 Hib, 2 Hic, 1 Hid, 1 Hie, 2 Hif and 10 were non-typeable (NT). All 43 Hia were biotype II, sequence type (ST)-23. Three related STs were found among the Hib isolates: ST-95 (n=9), ST-635 (n=2) and ST-44 (n=1). Both Hif belonged to ST-124 and the 2 Hic were typed as ST-9. The remaining Hid (ST-1288) and Hie (ST-18) belonged to 2 separate clones. Of the 10 NT strains, 3 were typed as ST-23 and the remaining 7 isolates each belonged to a unique ST. Eight Hib and 1 NT-Hi were found to be resistant to ampicillin due to β-lactamase production. No resistance to other antibiotics was detected. Conclusion: During the period of 2000–2012, Hia was the predominant serotype causing invasive disease in Nunavut. This presents a public health concern due to an emerging clone of Hia as a cause of invasive H. influenzae disease and the lack of published guidelines for the prophylaxis of contacts. The clonal nature of Hia could be the result of spread within an isolated population, and/or unique characteristics of this strain to cause invasive disease. Further study of Hia in other populations may provide important information on this emerging pathogen. No antibiotic resistance was detected among Hia isolates; a small proportion of Hib and NT-Hi isolates demonstrated resistance to ampicillin due to β-lactamase production.